A collection of library books that elementary school students are interested in - Siti Maysyarotul Masruroh; Fachri Helmanto (LADU: Journal of Languages and Education, 2022)
Background: Interest in reading can be interpreted as a desire to encourage someone to read books available in the library. Purpose: The aims of this research is to find out which types of books are most liked and interested by students. Design and methods: The research was conducted using a descriptive analytical case study, the method used was a mixed method. by using quantitative and qualitative approaches. The data obtained are using documents, observations and interviews. This research was conducted on 55 students in grade 1.A and grade 3A at Aligarh Islamic Elementary School. Results: The result of this study reveals there are 79 books that students like and are interested in. The books that students like the most are books with pictures.